2019
DOI: 10.1371/journal.pone.0223531
|View full text |Cite
|
Sign up to set email alerts
|

In vivo human lower limb muscle architecture dataset obtained using diffusion tensor imaging

Abstract: ‘Gold standard’ reference sets of human muscle architecture are based on elderly cadaveric specimens, which are unlikely to be representative of a large proportion of the human population. This is important for musculoskeletal modeling, where the muscle force-generating properties of generic models are defined by these data but may not be valid when applied to models of young, healthy individuals. Obtaining individualized muscle architecture data in vivo is difficult, however diffusion tensor magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 72 publications
5
77
2
Order By: Relevance
“…Here, a similar method to that described previously (Charles et al ., 2019; Charles et al ., 2019) is used to estimate subject‐specific muscle architecture data from 31 muscles of the right lower limb from each subject. This involves the use of two MRI sequences, T1‐weighted anatomical turbo spin‐echo (TSE) to estimate muscle volumes and visualise muscle attachment points, and diffusion tensor imaging (DTI) to estimate muscle fibre lengths and pennation angles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, a similar method to that described previously (Charles et al ., 2019; Charles et al ., 2019) is used to estimate subject‐specific muscle architecture data from 31 muscles of the right lower limb from each subject. This involves the use of two MRI sequences, T1‐weighted anatomical turbo spin‐echo (TSE) to estimate muscle volumes and visualise muscle attachment points, and diffusion tensor imaging (DTI) to estimate muscle fibre lengths and pennation angles.…”
Section: Methodsmentioning
confidence: 99%
“… Generic young (GY) – Individualised musculoskeletal geometry with muscle force‐generating properties from young, healthy individuals (age – 28 ± 4 years; body mass – 71.9 ± 11 kg). This is a combined average of the data collected in the present study and a previously published in vivo data set collected using similar methods (Charles et al ., 2019). Relative to the elderly generic data, the muscles within this data set are characterised by higher muscle volumes and F max values, longer fibre lengths (particularly in more distal functional groups) and larger pennation angles (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct comparisons about the proximo-distal variability in SM architectural is difficult to make since many studies have either measured from a single location or calculated the mean of several locations prior to subsequent analyses. 3,4,12,20,43 However, in two cadaveric studies, the pennation angle of the SM ( N = 8 limbs) was reported as 16 ± 2.4 degrees 3 and ( N = 22 limbs) 15.1 ± 3.4 degrees 4 with these measures calculated from the mean of proximal, middle, and distal locations along the SM. We calculated the whole muscle mean of pennation angle measures across all three locations along the SM as 15.4 ± 4.9 degrees, which is consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of DTI acquisitions requires many post‐processing steps for calculation of the DTI indices, which have been almost entirely automated—for more details see, eg, Reference 11 . However, segmentation of all the leg muscles, necessary for quantification, is a time‐consuming manual process, in which the accuracy and reproducibility may be operator dependent 12 .…”
Section: Introductionmentioning
confidence: 99%